The Effectiveness of Probiotic Supplementation in Treatment Stunting in Children - Norma Farizah Fahmi; Dwi Aprilia Anggraini; Vivin Wijiastutik (Universitas STRADA Indonesia, 2025)
Background: Stunting is a growth disorder in toddlers that is not normal, such as height or body length measurement results for children of the same age. Malnutrition is an indicator of social and political instability because it represents many people with diverse problems related to poverty, food insecurity, and poor hygiene and health. Purpose: The purpose of this study was to determine the effect of giving probiotics to children who experience stunting. Methods: This study uses a quantitative quasi-experimental design research type, with the design used being Non-Equivalent Pretest-posttest with control group design. In this study, there were 2 groups, namely the Probiotic therapy group and the control group with a total sample of 20. Data analysis conducted was Paired T-test and Independent T-test. Results: The results of the analysis showed that there was no difference in weight, height, or head circumference between the intervention and control groups. Conclusion: This indicates that the administration of probiotics did not have a significant effect on children's anthropometric values.